2019
DOI: 10.1039/c9nr05068j
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and hexa-palladium doped silver nanoclusters stabilized by dithiolates

Abstract: Structurally precise palladium doped silver-nanoclusters [PdAg20] and [Pd6Ag14(S)] stabilized by twelve dithiophosphate ligands have been isolated. The latter is the first example where a hexa-palladium(0) core is embodied within a silver(i) cluster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 48 publications
2
48
0
Order By: Relevance
“…The high-resolution Ag 3d XPS spectrum (Figure 2c) of the 0.5Ag-BT composite can be fitted into two groups of BE peaks, whereby the stronger ones at 367.5 (3d 5/2 ) and 373.5 (3d 3/2 ) eV are attributed to the metallic Ag species, and others with relatively weak intensities located at 368.2 (3d 5/2 ) and 374.2 (3d 3/2 ) eV correspond to Ag(I) species. 45,46 This indicates that the metallic Ag-nanoparticle-decorated composite coexists with a very small number of Ag(I) species that may not be photoreduced during the photodeposition process. Moreover, the 0.5Ag-BT(tw) composite, derived from a similar photodeposition process of the 0.5Ag-BT-yMn composites but without the addition of MnSO 4 solution and while extending the light illumination time from 0.5 to 1.0 h, still exhibits an obvious signal of the Ag(I) species.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution Ag 3d XPS spectrum (Figure 2c) of the 0.5Ag-BT composite can be fitted into two groups of BE peaks, whereby the stronger ones at 367.5 (3d 5/2 ) and 373.5 (3d 3/2 ) eV are attributed to the metallic Ag species, and others with relatively weak intensities located at 368.2 (3d 5/2 ) and 374.2 (3d 3/2 ) eV correspond to Ag(I) species. 45,46 This indicates that the metallic Ag-nanoparticle-decorated composite coexists with a very small number of Ag(I) species that may not be photoreduced during the photodeposition process. Moreover, the 0.5Ag-BT(tw) composite, derived from a similar photodeposition process of the 0.5Ag-BT-yMn composites but without the addition of MnSO 4 solution and while extending the light illumination time from 0.5 to 1.0 h, still exhibits an obvious signal of the Ag(I) species.…”
Section: Resultsmentioning
confidence: 99%
“…SCXRD and X‐ray absorption fine structure (XAFS) showed that a single atom of Ir, Pd or Pt exclusively occupies the central position of Au 13 (8e) and Ag 13 (8e) to form Ir/Pd/Pt@Au 12 and Pd/Pt@Ag 12 , respectively. [ 191–208 ] The selective doping of Ir/Pd/Pt at the center of Au 13 (8e) [ 191–201 ] is ascribed to the stronger Ir/Pd/PtAu bonds compared to the AuAu bonds and may contribute to the higher stability in Pd/Pt@Au 12 . [ 198,209 ] The structure of Pd/Pt@Ag 12 was also explained in a similar manner.…”
Section: Effect Of Doping: Spherical Superatomsmentioning
confidence: 99%
“…[ 198,209 ] The structure of Pd/Pt@Ag 12 was also explained in a similar manner. [ 202–208 ] In contrast, SCXRD revealed that more than single Ag atoms are preferentially located at the surface sites of the Au 13 (8e) core, resulting in the formation of Au@Ag x Au 12– x . [ 210–220 ] The single Au atom can be selectively doped to the central position of Ag 13 (8e) to form Au@Ag 12 .…”
Section: Effect Of Doping: Spherical Superatomsmentioning
confidence: 99%
“…59,[119][120][121][122] Similar improvement in stability and catalytic performance has been observed for atom-precise Ag-based bimetallic clusters. [123][124][125][126] While most of the existing studies have reported the catalytic activities of bimetallic clusters with protecting ligands intact, Xie et al reported the enhanced catalytic activity of thermally activated Pd 1 Au 24 (SC 12 H 25 ) 18 clusters on multiwalled carbon nanotube supports. 59 Their results showed that no activity was found for unactivated Pd 1 Au 24 (SC 12 H 25 ) 1 and Au 25 (SC 12 H 25 ) 18 systems, but activated catalysts were active for aerobic oxidation of benzyl alcohol.…”
Section: Discussionmentioning
confidence: 99%